Matter-antimatter asymmetry and non-inertial effects - Silveira, Vinicius Medeiros Gomes da (2021)
We investigate non-inertial effects on CP-violating processes using a model, based on the framework of quantum field theory in curved spacetimes, devised to account for the decay of accelerated particles. We show that the CP violation parameter for the decay of accelerated kaons into two pions decreases very slightly as very high accel erations are achieved, implying decreased asymmetry between matter and antimatter in this regime. We discuss the relationship between these results and cosmological processes surrounding matter-antimatter asymmetry and argue that, due to the connection between non-inertial and thermal phenomena established by the Unruh effect, this kind of computa tion may prove useful in furthering the understanding of thermodynamical effects in curved spacetimes.